PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN NON – PNS DIREKTORAT JENDERAL PENDIDIKAN SEKOLAH MENENGAH ATAS KEMENTRIAN PENDIDIKAN BUDAYA RISET DAN TEKNOLOGI) JAKARTA SELATAN - Uli, Kharisma; Suherman, Herry (Journal of Research and Publication Innovation, 2024)
This research aims to find out how much influence leadership style and work motivation have on employee performance (case study of NON – PNS employees of the Directorate General of Senior High School Education, Ministry of Education, Culture, Research and Technology) South Jakarta. The sampling technique used saturated sampling and a sample of 73 respondents was obtained. Data collection used SPSS 27. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, coefficient of determination analysis in hypothesis testing. The results of this research show that leadership style partially influences employee performance t count > t table or (4.718 > 1.994) with a significant value (0.000 < 0.05) while partially work motivation influences employee performance with t count > t table or (8.964 > 1.994) with a significant value (0.000 < 0.05). Simultaneously leadership style and work motivation influence employee performance with a calculated F value > F table or (40.711 > 3.13) with a significant level of (0.000 < 0.05). The contribution of leadership style and work motivation influences employee performance by 53.8%.